5g spectrum and standards - Varrall, Geoffrey (Artech House mobile communications series., 2016)
This new resource provides key insight into future 5G radio systems and the technical and economic impact on industries, communities and end-users. The book offers a comprehensive understanding of the options available for teams tasked with bringing 5G products and services to market or developing supporting standards and regulatory frameworks. Readers find contemporary examples of millimeter band radio hardware including 60 GHz and V band and E Band point to point radio. This book demonstrates the profound progress with 4G radio signal processing and RF hardware to reveal its potential applicability to 5G radio systems. It shows how 5G systems are capable of delivering data rates that are ten to one hundred times faster than 4G systems. Developments in spatial processing and beam forming in local area radio networks are presented and the challenge of scaling these systems to wide area radio is explored. This book reviews military and space radio and automotive radar innovation with direct relevance to 5G radio design.